Effect of NaCl-Stress on Metabolism of NO3-, NH4+ and NO2- at Several Rice Varieties - Utama, M Zulman Harja (JOURNAL OF TROPICAL SOILS, 2010)
Effect of NaCl-Stress on  Metabolism of NO3-, NH4+  and NO2- at Several Rice Varieties (MZH Utama):  This study was conducted to evaluate the effect of NaCl-stress on metabolism of  NO3-, NH4+  and NO2-  at several rice varieties.  The results showed that an addition of  NaCl had lesser effect on NaCl-tolerant varieties as compared to NaCl-sensitive in term of reduction in NO3-, NH4+,  and NO2- uptake. Rice adaptation ability to NaCl stress occurred through the mechanism of NO3-, NH4+, and N02- metabolism physiology. It was  indicated by the difference concentration of NO3-, NH4+ and N02- between the tolerant (Cisadane), moderate (Batang Lembang, Rendah Kuning, and Batang Piaman) and sensitive (IR 66) varieties. Concentration of NH4+ and N02-  of tolerant rice (Cisadane) at NaCl treatment were about 1.16 and 2.6 times higher than that at control, respectively, while concentration of NO3- was only 0.03 times lower than control.  In contrast, concentration of NO3-, NH4+, and N02- of sensitive rice (IR 66), were about 0.09, 0.27, and 0.41 times lower than that in control respecting at NaCl treatment, respectively.